Pre-emptive intervention versus treatment as usual for infants showing early behavioural risk signs of autism spectrum disorder: a single-blind, randomised controlled trial. (September 2019) - Whitehouse, Andrew J O; Varcin, Kandice J; Alvares, Gail A; Barbaro, Josephine; Bent, Catherine; Boutrus, Maryam; Chetcuti, Lacey; Cooper, Matthew N; Clark, Alena; Davidson, Emma; Dimov, Stefanie; Dissanayake, Cheryl; et al.
Summary: Background: Great interest exists in the potential efficacy of prediagnostic interventions within the autism spectrum disorder prodrome, but available evidence relates to children at high familial risk. We aimed to test the efficacy of a pre-emptive intervention designed for infants showing early behavioural signs of autism spectrum disorder. Methods: In this single-blind, randomised controlled trial done at two specialist centres in Australia, infants aged 9–14 months were enrolled if they were showing at least three early behavioural signs of autism spectrum disorder on the Social Attention and Communication Surveillance-Revised (SACS-R) 12-month checklist. Infants were randomly assigned (1:1) to receive a parent-mediated video-aided intervention (iBASIS-VIPP) or treatment as usual. Group allocation was done by minimisation, stratified by site, sex, age, and the number of SACS-R risk behaviours. Assessments were done at baseline (before treatment allocation) and at the 6 month endpoint. The primary outcome was Autism Observation Scale for Infants (AOSI), which measures early behavioural signs associated with autism spectrum disorder. Secondary outcomes were a range of infant and caregiver outcomes measured by Manchester Assessment of Caregiver–Infant interaction (MACI), Mullen Scales of Early Learning (MSEL), Vineland Adaptive Behaviour Scales, 2nd edition (VABS-2), MacArthur-Bates Communicative Development Inventory (MCDI), and Parenting Sense of Competence (PSOC) scale. This trial is registered with Australian New Zealand Clinical Trials Registry, number ANZCTR12616000819426. Findings: Between June 9, 2016, and March 30, 2018, 103 infants were randomly assigned, 50 to the iBASIS-VIPP group and 53 to the treatment-as-usual group. After the intervention, we observed no significant differences between groups on early autism spectrum disorder behavioural signs measured by the AOSI (difference estimate −0·74, 95% CI −2·47 to 0·98). We also observed no significant differences on secondary outcomes measuring caregiver non-directiveness (0·16, −0·33 to 0·65), caregiver sensitive responding (0·24, −0·15 to 0·63), and infant attentiveness (−0·19, −0·63 to 0·25) during parent–child interactions (MACI), as well as on researcher-administered measures of receptive (1·30, −0·48 to 3·08) and expressive language (0·54, −0·73 to 1·80), visual reception (0·31, −0·77 to 1·40), and fine motor skills (0·55, −0·32 to 1·41) using the MSEL. Compared with the treatment-as-usual group, the iBASIS-VIPP group had lower infant positive affect (−0·69, −1·27 to −0·10) on the MACI, but higher caregiver-reported receptive (37·17, 95% CI 10·59 to 63·75) and expressive vocabulary count (incidence rate ratio 2·31, 95% CI 1·22 to 4·33) on MCDI, and functional language use (difference estimate 6·43, 95% CI 1·06 to 11·81) on VABS. There were no significant group differences on caregiver-reported measures of MCDI infant gesture use (3·22, −0·60 to 7·04) and VABS social behaviour (3·28, −1·43 to 7·99). We observed no significant differences between groups on self-reported levels of parenting satisfaction (difference estimate 0·21, 95% CI −0·09 to 0·52), interest (−0·23, −0·62 to 0·16) and efficacy (−0·08, −0·38 to 0·22) on PSOC. Interpretation: A pre-emptive intervention for the autism spectrum disorder prodrome had no immediate treatment effect on early autism spectrum disorder symptoms, the quality of parent–child interactions, or researcher-administered measures of developmental skills. However, we found a positive effect on parent-rated infant communication skills. Ongoing follow-up of this infant cohort will assess longer-term developmental effects. Funding: Western Australia Children's Research Fund, Autism Cooperative Research Centre, La Trobe University, and Angela Wright Bennett Foundation.